2022
DOI: 10.2196/39204
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mental Health Interventions for Depression: Scoping Review of User Engagement

Abstract: Background While many digital mental health interventions (DMHIs) have been found to be efficacious, patient engagement with DMHIs has increasingly emerged as a concern for implementation in real-world clinical settings. To address engagement, we must first understand what standard engagement levels are in the context of randomized controlled trials (RCTs) and how these compare with other treatments. Objective This scoping review aims to examine the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Previous work has shown that despite interest in mental health apps among students, the use of these apps can be limited [57][58][59]. Building on the earlier work whose methodology we replicated, our ndings allowed us to uncover various factors associated with DMHA use in the academic community and, more particularly, its students.…”
Section: Discussionmentioning
confidence: 71%
“…Previous work has shown that despite interest in mental health apps among students, the use of these apps can be limited [57][58][59]. Building on the earlier work whose methodology we replicated, our ndings allowed us to uncover various factors associated with DMHA use in the academic community and, more particularly, its students.…”
Section: Discussionmentioning
confidence: 71%
“…In spite of the power of AI (artificial intelligence) for deriving insights from medical records 3 or the sensitivity of digital phenotyping 4 , diagnosis still involves a human interviewer collecting patient data. Similarly, while companies creating autonomous agents and digital therapeutics have been funded robustly, most studies show that psychotherapy requires a human in the loop to optimize engagement 5 . Nevertheless, there is a continuing opportunity for objective data to augment subjective data through digital measures of sleep or activity or sociality 6 .…”
Section: Lessons From Actmentioning
confidence: 99%
“…Compared to in‐person interventions, DMHIs can also be more accessible, standardized, cost‐effective, and convenient. Nevertheless, studies indicate that engagement and adherence vary widely in DMHIs, suggesting a need for standardized reporting guidelines to facilitate comparisons with other forms of care (Lipschitz et al., 2022).…”
Section: Introductionmentioning
confidence: 99%